KUALITAS PRODUK, DESAIN PRODUK DAN CELEBRITY ENDORSEMENT TERHADAP KEPUTUSAN PEMBELIAN - Vionita, Rina; S, Budi Setiawan; Zebua, Jefri Saputra; Putri, Yorie Nadila (Universitas Bina Bangsa, 2024)
The rapidly growing business world has increased business competition, including in the automotive sector, especially motorcycles. From these demands, business actors must pay attention to the factors that influence purchasing decisions. This study aims to analyze the effect of product quality, product design and celebrity endorsement on purchasing decisions on Honda Scoopy Stylish motorcycles at PT. Hayati Pratama Mandiri Padang. This research is included in quantitative research. The population of this study is all consumers who purchase Scoopy motorcycles at PT. Hayati Pratama Mandiri, Padang. The research sample was determined using total sampling so that 138 consumers were obtained. The data in this study were taken through observation, interview, and questionnaire techniques using research instruments that were tested for validity and reliability first. The data obtained were explained descriptively and inferentially. Before conducting the hypothesis test, normality, multicollinearity, and multiple regression analysis were tested. The hypothesis test in this study used the T Test. The results of the study obtained variables that increased the purchase decision for the Scoopy Stylish motorcycle, namely product quality and product design. However, celebrity endorsement had a significant effect on Purchasing Decisions. So, the results of this study can be used as a consideration for PT. Hayati Pratama Mandiri in particular and Honda Company to always maintain product quality and come up with the best designs for their products with the hope that purchasing decisions will always be maintained and increased